2015
DOI: 10.1073/pnas.1516131112
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Hsp70 delays senescence and improves cognitive function in aging mice

Abstract: Molecular chaperone Heat Shock Protein 70 (Hsp70) plays an important protective role in various neurodegenerative disorders often associated with aging, but its activity and availability in neuronal tissue decrease with age. Here we explored the effects of intranasal administration of exogenous recombinant human Hsp70 (eHsp70) on lifespan and neurological parameters in middle-aged and old mice. Long-term administration of eHsp70 significantly enhanced the lifespan of animals of different age groups. Behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 56 publications
4
59
0
1
Order By: Relevance
“…A few studies have demonstrated sex-biased expression of HSP genes and suggest that some HSP genes have essential roles in reproduction, such as in the embryonic development of mammals and insects (Neuer et al 2000;Hahn & Lanzaro 2005). In mice, administration of exogenous recombinant human hsp70 significantly enhanced the lifespan of the mice and improved behavioral, learning, and memory in old mice (Bobkova et al 2015). Figure 1 Comparison of the expression profiles of nine selected genes between male and female adults of Plodia interpunctella.…”
Section: Resultsmentioning
confidence: 99%
“…A few studies have demonstrated sex-biased expression of HSP genes and suggest that some HSP genes have essential roles in reproduction, such as in the embryonic development of mammals and insects (Neuer et al 2000;Hahn & Lanzaro 2005). In mice, administration of exogenous recombinant human hsp70 significantly enhanced the lifespan of the mice and improved behavioral, learning, and memory in old mice (Bobkova et al 2015). Figure 1 Comparison of the expression profiles of nine selected genes between male and female adults of Plodia interpunctella.…”
Section: Resultsmentioning
confidence: 99%
“…Senescence, a process which prevents the propagation of cells with mutated DNA, is mainly protected by the Oncogene-induced senescence (OIS) barrier (36). As studies have shown that the OIS barrier was shown to be bypassed with the upregulation of Hsp70, it is obvious that the protein has a major role in regulating senescence signaling pathways (58, 59). Experiments have shown that inhibition of Hsp70 has induced senescence in the cells by activating cell signaling pathways involving p53 and p21 (20, 58, 59).…”
Section: Hsp70 and Pcamentioning
confidence: 99%
“…As studies have shown that the OIS barrier was shown to be bypassed with the upregulation of Hsp70, it is obvious that the protein has a major role in regulating senescence signaling pathways (58, 59). Experiments have shown that inhibition of Hsp70 has induced senescence in the cells by activating cell signaling pathways involving p53 and p21 (20, 58, 59). Furthermore, studies have also demonstrated that the silencing of Hsp70 has led to the depletion of Forkhead box protein M1 (FOXM1) and HuR, major role-players against OIS (60, 61).…”
Section: Hsp70 and Pcamentioning
confidence: 99%
“…For example, eHSP70 has been reported to stimulate neutrophil microbicidal capacity [114] and chemotaxis [115] and recruitment of natural killer (NK) cells [116], as well as cytokine production by immune cells [73,117]. In addition, eHSP70 has been recently hypothesized to be involved in motor neuron cell protection under stress conditions and neurodegenerative diseases [63,118]. However, contrarily to that which occurs when HSP70 is within the intracellular space (iHSP70), when exported to the extracellular space (eHSP70), it functions as a stress signaling and pro-inflammatory molecule possibly by acting via TLR2 and TLR4 (see, for instance, ref.…”
Section: Anti-inflammatory Role Of Intracellular Hsp70mentioning
confidence: 99%
“…It is of note, indeed, that fibromyalgia is associated with abnormal protein ubiquitination and HS response pathways [169], at the same time, fibromyalgia predisposes the patient to an increased risk for developing age-related diseases prematurely, suffering earlier cognitive and physical decline and experiencing earlier mortality [16]. On the other hand, long-term intranasal administration of recombinant HSP70 (in order for HSP70 to reach different cerebral structures intracellularly, so to enhance iHSP70) to middle-aged and old mice has convincingly demonstrated that iHSP70 enhances animal lifespan, improves learn, memory, and locomotor and exploratory activities in old mice [118]. This suggests that pharmacological administration of tissue-directed iHSP70 may be of value in reverting aging-associated disorders in humans.…”
Section: Suppression Of the Heat Shock Response In Agerelated Degenermentioning
confidence: 99%